AB0742 ACHIEVEMENT OF PASDAS LOW DISEASE ACTIVITY AND VERY LOW DISEASE ACTIVITY IN PATIENTS WITH PSORIATIC ARTHRITIS TREATED WITH CERTOLIZUMAB PEGOL OVER 4 YEARS AND THE OVERLAP WITH DAPSA AND MDA DISEASE ACTIVITY TARGETS. (June 2019) - Coates, Laura C.; Merola, Joseph F.; Fitzgerald, Oliver; Kavanaugh, Arthur; Gottlieb, Alice B.; Tillett, William; Bauer, Lars; Hoepken, Bengt; Nurminen, Tommi; Mease, Philip J.; Helliwell, Philip; Heijde, Désirée van der
Abstract : Background: Psoriatic arthritis Disease activity Score (PASDAS), 1 Disease activity index for Psoriatic arthritis (DAPSA), 2 and the minimal disease activity (MDA) criteria 3 are instruments recommended for evaluating disease activity (DA) in psoriatic arthritis (PsA). RAPID-PsA demonstrated the sustained efficacy of certolizumab pegol (CZP) across the spectrum of PsA symptoms. 4 a substantial proportion of patients (pts) completing 4 years' treatment achieved DA targets; ∼75% reached DAPSA low DA (LDA) or remission (REM), and almost 60% had MDA (≥5/7 MDA criteria), half of whom also achieved very low DA (VLDA) (7/7 MDA criteria). 5 Objectives: To report the proportion of pts who achieved PASDAS VLDA and LDA over 216 weeks' (wks') CZP treatment, and the overlap in pts achieving PASDAS, DAPSA and MDA. Methods: RAPID-PsA (NCT01087788 ) was double-blind and placebo-controlled to Wk24, dose-blind to Wk48, and open-label (OL) to Wk216. 5 Outcomes reported for pts randomised to CZP at Wk0 (200 mg every 2 wks or 400 mg every 4 wks, following a 400 mg loading dose at Wks0/2/4) are PASDAS change from baseline (CFB); pts achieving PASDAS LDA (>1.9−<3.2), PASDAS VLDA (≤1.9), DAPSA LDA (>4−≤14), DAPSA REM (≤4), MDA and VLDA to Wk216; and the overlap in pts achieving PASDAS VLDA, DAPSA REM, and VLDA, at Wk216. Data are summarized for observed cases per visit. Pts withdrawing between scheduled visits had their final assessment values assigned to the next scheduled visit timepoint. Results: Of 409 pts randomised, 273 received CZP from Wk0, of whom 248 (90.8%) completed Wk24 and 183 (67.0%) completed Wk216. The mean (SD) baseline PASDAS was 6.0 (1.0): in the high DA range, CFB at Wk216 was −3.4 (1.5). Of pts completing Wk216, 66.3% (118/178) were in PASDAS LDA or VLDA (PASDAS VLDA: 36.5% [n=65]): less than the proportion reaching DAPSA LDA or REM (76.2%), but more than those achieving MDA or VLDA (57.8%) (Figure a ). At Wk216, of pts achieving PASDAS VLDA, a large proportion (71% [46/65]) had VLDA based on MDA criteria (Figure B1 ) and most (94% [61/65]) achieved DAPSA REM (Figure B2 ). Almost all pts achieving VLDA (96.1% [50/52]) were also in DAPSA REM (Figure B3 ). After 4 years' CZP treatment, 25.8% (46/178) pts achieved the PASDAS VLDA, DAPSA REM and VLDA. Conclusion: A substantial proportion of pts completing 4 years' CZP treatment achieved PASDAS LDA or VLDA, and the vast majority who achieved PASDAS VLDA at Wk216 also reached DAPSA REM and/or VLDA. 1 in 4 pts achieved the most stringent DA target with all 3 instruments. References: [1] Helliwell P. Ann Rheum Dis2013;72:986–91; 2. Schoels M. Ann Rheum Dis 2016;75:811–18; 3. Coates L. Ann Rheum Dis2010;69:48–53; 4. van der Heijde D. RMD Open 2018;4:e000582. Acknowledgement: We thank the patients who participated. This study was funded by UCB Pharma, medical writing by Hinal Tanna, Costello Medical, UK. Disclosure of interests: Laura C Coates Grant/research support from: abbVie, Celgene, Lilly, Novartis and Pfizer, Consultant for: abbVie, amgen, BMS, Celgene, Galapagos, Gilead Sciences inc., Janssen, Lilly, Novartis, Pfizer, Prothena Corp and UCB, Joseph F. Merola Consultant for: Biogen IDEC, abbvie, amgen, Eli Lilly and Company, Novartis, Pfizer, Janssen, UCB, Samumed, Celgene, Sanofi Regeneron, Merck, and GSK, Oliver FitzGerald: None declared, arthur Kavanaugh Grant/research support from: UCB Pharma, alice B Gottlieb Grant/research support from: PI: incyte Corporation, Janssen-Ortho inc., Lilly ICOS LLC, Novartis, UCB, XBiotech, Consultant for: abbVie, Dermira, incyte Corporation, Lilly ICOS LLC, Novartis, Sun Pharmaceutical industries Ltd., avotres (unpaid), XBiotech (unpaid), Speakers bureau: abbVie, Eli Lilly and Company, Janssen Biotech; advisory board: Bristol-Myers Squibb, Celgene Corporation, Janssen Biotech, Janssen-Ortho inc., LEO Pharma, Novartis, UCB, William Tillett Grant/research support from: abbVie, Celgene, and Lilly, Consultant for: abbVie, Celgene, Lilly, Novartis, and Pfizer, Speakers bureau: abbvie, Celgene, Lilly, Janssen, Novartis, UCB, and Pfizer, Lars Bauer Employee of: Employee of UCB Pharma, Bengt Hoepken Employee of: Employee of UCB Pharma, Tommi Nurminen Employee of: Employee of UCB Pharma, Philip J Mease Grant/research support from: abbVie, amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: abbVie, amgen, BMS, Galapagos, Gilead Sciences, inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: abbVie, amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB, Philip Helliwell Grant/research support from: Paid to charity: from abbVie, Janssen and Novartis, Consultant for: Paid to charity: from abbVie, amgen, Pfizer, and UCB and Celgene. Paid to self: from Celgene and Galapagos, Désirée van der Heijde Consultant for: abbVie, amgen, astellas, astraZeneca, Bristol-Myers Squibb, Boehringer ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, GlaxoSmithKline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, Union Chimique Belge